Discourse on Suicide among Students at Yogyakarta Universities - Ajy Waskyto Sugiyanto, Bagus (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2024)
Student suicide as a recent phenomenon is always discussed from a psychological and individualist perspective. Therefore, this research has a problem formulation of how regulated statements or discourse regarding DIY student suicide are formed. This research seeks to reveal knowledge about suicide by students. This knowledge is created by discourse. In Archeology of Knowledge (1972: 80), Foucault defines discourse as the